2004
DOI: 10.2527/2004.82102995x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Se on selenoprotein activity and thyroid hormone metabolism in beef and dairy cows and calves

Abstract: Although Se is essential for antioxidant and thyroid hormone function, factors influencing its requirement are not well understood. A survey and two experiments were conducted to determine the influence of cattle breed and age on selenoprotein activity and the effect of maternal Se supplementation on cow and calf selenoprotein activity and neonatal thyroid hormone production. In our survey, four cowherds of different ages representing three breeds were bled to determine the influence of breed and age on erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
31
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 46 publications
13
31
1
5
Order By: Relevance
“…Colostrum Se was increased with supranutritional dietary Se, similar to previous reports (Abdelrahman and Kincaid, 1995;Rowntree et al, 2004;Hefnawy et al, 2008;Swanson et al, 2008;Moeini et al, 2009). Additionally, Se remained increased in milk throughout the first 20 d of lactation, despite a decrease in both concentration of and total Se in milk.…”
Section: Colostrum and Milk Nutrient Compositionsupporting
confidence: 78%
“…Colostrum Se was increased with supranutritional dietary Se, similar to previous reports (Abdelrahman and Kincaid, 1995;Rowntree et al, 2004;Hefnawy et al, 2008;Swanson et al, 2008;Moeini et al, 2009). Additionally, Se remained increased in milk throughout the first 20 d of lactation, despite a decrease in both concentration of and total Se in milk.…”
Section: Colostrum and Milk Nutrient Compositionsupporting
confidence: 78%
“…At 45 th , 90 th and 180 th days, group II and group IV had signifi cantly (P<0.001) higher levels of Se as compared to group I and III, indicating that the plasma Se levels in the groups supplemented with Se was increased. Similar to our results various researchers reported that supplemental Se increased the blood levels of Se in young cattle bulls (Pherson and Johnson, 1985), Holstein cows (Weiss et al, 1990) and in Hereford cows (Rowntree et al, 2004). The activity of different antioxidant enzymes, i.e.…”
Section: Resultssupporting
confidence: 81%
“…Selenium, in particular, has been utilized by biological systems because it endows proteins with unique coordination, catalytic and electron transfer properties (Rowntree et al, 2004;Suzuki, 2005). These properties have been employed by organisms in key functions in a variety of pathways, resulting in dependence of organisms on the chemical form and level of Se in diets.…”
Section: Introductionmentioning
confidence: 99%